The General History of the Middle Ages at the V. Babeş University of Cluj (1951-1952) - COSTEA, Ionuț (Studia Universitatis Babeș-Bolyai Historia, 2020)
The General History of the Middle Ages at the V. Babeş University of Cluj (1951-1952). The 1948 education reform represented, besides a new institutional architecture transposed in accordance with the model of the soviet universities, a process of recycling professors. The process of changing the teaching staff was carried out on at least two levels – the definitive or temporary elimination (sometimes accompanied by incarceration) from the education system on the one hand, and the exertion of severe surveillance and intimidation, thus remodelling the discourse and the behaviour in the spirit of the socialist realist “cultural revolution” on the other hand. The study shed light on a method that led to the expulsion of the professors was the public defamation, the accusation of immorality and of their lack of understanding of the new political transformations of the country, thus labelling the professors as “enemies of the people”. The atmosphere of fear and humiliation was sustained through press campaigns of defamation. Especially the younger university professors were instructed to attack, in the press, the more professionally well reputed and publicly well-known professors. These articles contained not only analyses of the professors’ works and ideas, but also their dismantling, their “exposé” and their human undermining. This paper is a case study on a professor from medieval department of Cluj university, Francisc Pall at the beginning of 1950s years. Rezumat: Istoria generală a Evului Mediu la Universitatea V. Babeş din Cluj (1951-1952). Reorganizarea învăţământului superior din România ca urmare a reformei din 1948 a însemnat şi pentru Universitatea din Cluj şi implicit pentru învăţământul de istorie o schimbare radicală atât a modului de organizare instituţională cât şi a conţinutului procesului didactic. Modelarea instituţională după structurile didactice sovietice şi predominanţa caracterului ideologic în spiritul dogmatic al marxism-leninismului al conţinutului învăţământului au devenit trăsăturile fundamentale ale sistemului de învăţământ din România. Frământările organizării administrative se reflectă şi la nivelul structurilor facultăţii de istorie. Astfel, iniţial, între alte structuri ale Facultăţii de Istorie a funcţionat şi o Catedră Generală a Evului Mediu, colectivul didactic activând sub această formă până în luna mai a anului 1952, de când s-a format o singură catedră de istorie universală, cuprinzând antichitatea, epocile medievală, modernă şi contemporană. Studiul de faţă discută acest procesul instituţional de transformare instituţională a studiilor de Ev Mediu şi impactul lor asupra destinului profesional a profesorului Francisc Pall. Cuvinte-cheie: comunism, România, reforma educaţiei, revoluţie culturală, violenţa, supraveghere.